2014
DOI: 10.1098/rspb.2013.3089
|View full text |Cite
|
Sign up to set email alerts
|

Honeybees (Apis mellifera) learn to discriminate the smell of organic compounds from their respective deuterated isotopomers

Abstract: The understanding of physiological and molecular processes underlying the sense of smell has made considerable progress during the past three decades, revealing the cascade of molecular steps that lead to the activation of olfactory receptor (OR) neurons. However, the mode of primary interaction of odorant molecules with the OR proteins within the sensory cells is still enigmatic. Two different concepts try to explain these interactions: the 'odotope hypothesis' suggests that OR proteins recognize structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 54 publications
(80 reference statements)
5
24
2
1
Order By: Relevance
“…The principal experimental evidence supporting the vibrational theory has been the deuterium isotope effect at the perceptual (behavioral) level (14,36,38). However, we find no experimental evidence supporting the theory at the molecular level.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The principal experimental evidence supporting the vibrational theory has been the deuterium isotope effect at the perceptual (behavioral) level (14,36,38). However, we find no experimental evidence supporting the theory at the molecular level.…”
Section: Discussioncontrasting
confidence: 51%
“…Earlier claims that human subjects can distinguish odors of acetophenone isotopomers (9,35) have been shown to be untrue (14,31). Recent studies indicate that Drosophila melanogaster can distinguish acetophenone isotopomers (36,37) and that Apis mellifera L., the honey bee, can be trained to discriminate pairs of isotopomers (38). These studies differ from earlier insect studies in which isotopomer discrimination was not found.…”
Section: Significancecontrasting
confidence: 56%
“…has arisen and has gained both supporters (13)(14)(15)(16) and detractors (17,18); the novelty of this incarnation of the VTO is ascribable to its nonthermal-and nonphoton-based mechanism. Turin's theory is a contemporary reincarnation of the more classical theory proposed by Dyson (19), Wright (20), and Wright and Serenius (21), where the activation of the olfactory receptor is performed-or sensitive to-the molecular vibrations of the olfactant.…”
mentioning
confidence: 99%
“…Additionally, more modern examinations of this theory with both humans and insect subjects have provided mixed and controversial results. (14,(16)(17)(18)(22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation